The Effect Of Online Customer Review, Online Customer Rating, And Customer Experience On Purchase Decision On Grabfood Services In East Java - Oktavia Amanda Putri Nabila; Evi Yulia (Sean Institute, 2025)
This study aims to determine the influence of online customer reviews, online customer ratings, and customer experience on purchase decisions on grabfood services in East Java. This study uses a type of quantitative research using a sample of 96 respondents. The data used in this study was obtained by distributing a questionnaire questionnaire that was analyzed using the SPSS version 26 tool. The results of the study showed that partially online customer reviews, online customer ratings, and customer experience had a significant and positive effect on purchase decesion. Then simultaneously the variables of online customer review, online customer rating, and customer experience have an influence on purchase decisions. Then the results of multiple linear regression show that the customer experience variable is the most dominant variable for purchase decisions.